ANALISIS PAPPASANG PONGGAWA PADA MASYARAKAT NELAYAN (PATORANI) DI KECAMATAN GALESONG SELATAN KABUPATEN TAKALAR - Handayani, Fitri; Hamsa, Akmal; Daeng, Kembong (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This study aims to describe the form of Pappasang ponggawa, reveal the meaning of Pappasang ponggawa and reveal the moral values contained in Pappasang ponggawa in fishing communities. This research is a qualitative study, using a qualitative descriptive design, which focuses on the form, meaning, and value of Pappasang ponggawa, obtained from ponggawa in South Galesong District through observation, interviews, and recording. The research instruments consisted of researchers, recorders, notebooks, and interview guidelines. The results revealed that the form of Pappasang ponggawa in the fishing community in South Galesong District, Takalar Regency, is a form of dialogue, pamali, and doangang which contains lexical, contextual, and connotative meanings. The moral values in the Pappasang are individual, social, and religious moral values